Indikasi Pelanggaran Hak Asasi Manusia dalam Memorandum of Understanding Kerjasama Migrasi Italia dan Libya periode 2017-2019: INDICATIONS OF HUMAN RIGHTS VIOLATIONS IN THE MEMORANDUM OF UNDERSTANDING COOPERATION ON ITALIAN AND LIBYAN MIGRATION FOR THE PERIOD 2017-2019 - Aulia, Nurul; Fikri Fahrul Faiz; Faiz, Fikri Fahrul (Fakultas Hukum Universitas Trisakti, 2023)
This research examines the Indications of Human Rights Violations in the Memorandum of Understanding (MoU) on Cooperation on Development, Combatting Illegal Immigration, Human Trafficking and Smuggling, and on Strengthening Border Security Between Italy and Libya for the 2017-2019 Period. The 2017-2019 period was chosen because the period shows the running of the agreement which was then extended in 2020, and uses descriptive qualitative research methods. This research is conducted through literature studies sourced from official documents, books journal articles, publications, articles that can be accessed through the internet, and other references. This research uses the concepts of International Human Rights Law and Human Security to answer various findings related to indications of human rights violations in the MoU on migration cooperation between Italy and Libya. The study found that there are indications of human rights violations against migrants and refugees including violations of the principle of non-refoulement, prevention and restriction of inflows that have the potential for continuing violations in the form of threats of arrest and detention without going through a fair process, to not fulfilling aspects of Human Security.